Pyrethroid Exposure Reduces Growth and Development of Monarch Butterfly (Lepidoptera: Nymphalidae) Caterpillars. Issue 2 (4th March 2021) - Krueger, Annie J; Hanford, Kathryn; Weissling, Thomas J; Vélez, Ana M; Anderson, Troy D
Abstract: Insecticide exposure has been identified as a contributing stressor to the decline in the North American monarch butterfly Danaus plexippus L. (Lepidoptera: Nymphalidae) population. Monarch toxicity data are currently limited and available data focuses on lethal endpoints. This study examined the 72-h toxicity of two pyrethroid insecticides, bifenthrin and β-cyfluthrin, and their effects on growth and diet consumption. The toxicity of bifenthrin to caterpillars was lower than β-cyfluthrin after 72 h. Survival was the most sensitive endpoint for bifenthrin, but diet consumption and caterpillar growth were significantly reduced at sublethal levels of β-cyfluthrin. Using AgDRIFT spray drift assessment, the aerial application of bifenthrin or β-cyfluthrin is predicted to pose the greatest risk to fifth-instar caterpillars, with lethal insecticide deposition up to 28 m for bifenthrin and up to 23 m for β-cyfluthrin from treated edges of fields. Low boom ground applications are predicted to reduce distances of lethal insecticide exposure to 2 m from the treated field edge for bifenthrin and β-cyfluthrin. Growth and survival of fifth-instar monarch caterpillars developing within the margins of a treated field may be significantly impacted following foliar applications of bifenthrin or β-cyfluthrin. These findings provide evidence that pyrethroid insecticides commonly used for soybean pest control are a potential risk to monarch caterpillars in agricultural landscapes.